Clinical Characteristics, Risk Factors, and Outcomes of Patients With Myocardial Injury due to Klebsiella pneumoniae Bloodstream Infections - Qingqing Chen; Panpan Xu; Zhihui Guan; Feizhen Song; Xinhua Luo; Xijiang Zhang; Chuming Zhang; Ronghai Lin; Cheng Zheng (Canadian Journal of Infectious Diseases and Medical Microbiology, 2025)
Conclusions: Older age (> 67 years), higher SOFA score (> 6), mechanical ventilation, and CVC in place were found to be significantly associated with an increased risk of myocardial injury. Clinical physicians should be alert to the potential for myocardial injury in elderly critically ill patients, especially those who are on mechanical ventilation and have indwelling CVC, in the event of KP-BSI.